Heat mitigation benefits of urban green and blue infrastructures: A systematic review of modeling techniques, validation and scenario simulation in ENVI-met V4 - Liu, Zhixin; Cheng, Wenwen; Jim, C.Y.; Morakinyo, Tobi Eniolu; Shi, Yuan; Ng, Edward (Building and environment, 2021)
Urban green and blue infrastructures (GBI) are considered an effective tool for mitigating urban heat stress and improving human thermal comfort. Many studies have investigated the thermal effects of main GBI types, including trees, green roofs, vertical greenings, and water bodies. Their physical characteristics, planting designs, and the surrounding urban-fabric traits may impact the resultant thermal effects. ENVI-met, a holistic three-dimensional modeling software which can simulate the outdoor microclimate in high resolution, has become a principal GBI research tool. Using this tool, the GBI studies follow a three-step research workflow, i.e., modeling, validation, and scenario simulation. For providing a systematic and synoptic evaluation of the extant research workflow, a comprehensive review was conducted on GBI-targeted studies enlisting ENVI-met as the primary tool. The findings of 79 peer-reviewed studies were analyzed and synthesised for their modeling, validation, and scenario simulation process. Special attention was paid to scrutinising their data sources, evaluating indicator selection, examining main analytical approaches, and distilling recommendations to improve the research workflow. This review provides researchers with an overview of the ENVI-met methodology and recommendations to refine research on GBI thermal effects.